Field resistance components of potato to late blight and their relative contribution towards disease resistance - and L.K. PAREEK, RANJANA CHAUHAN, B.P. SINGH (Indian Phytopathology, 2005)
Variation, genetic parameters and interrelationships analysis for components of field resistance to Phytophthora infestans in potato were studied using detached leaves from 60 genotypes of diploid wildI semicultivated tuber bearing Solanum species. The resistant genotypes had a longer latent period and lower lesion size and spore production than the susceptible genotypes. Significant inter- genotypic variability was recorded for all the components and Area Under Disease Progress Curve (AUDPC). Highest inter- genotypic variability was observed for lesion size and AUDPC and lowest for spore density. Genetic and phenotypic pathcoefficient analysis indicated lesion size to be the most important component of field resistance. The genetic correlation coefficients between the AUDPC and infection efficiency, latent period and spore density arose mainly because of their indirect effects on AUDPC via lesion size. Lesion size and AUDPC had a high. Genetic coefficient of variation, heritability and genetic advance.